SRYPHOMAT FOR TEACHING VOCABULARY - Mutayam, .; ., Regina; ., Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: Sryphomat is a prospective technique for teaching vocabulary, it is a combination technique of story, photographs and matching game. The aim of the technique is to enrich the students’ vocabulary namely; noun, pronoun and adjective. The story is to elicit the word while the photographs is to elicit the meaning of the word in the story. Then, the matching game is used to motivate the students to be more active in the classroom setting. ADDIE procedure is used to develop Sryphomat, the process was done through need analysis, design, development, implementation and evaluation. In this development research, the technique was implemented in large class that consisted of 24 students of sixth graders of SD Negeri 29 Kecamatan Pontianak Timur. One-Group Pretest and Posttest was conducted to investigate the effectiveness of Sryphomat toward students’ vocabulary. The result shown that this product was highly effective, the t = 9,02 and the ES is 1,08. The t-test is higher then t table of distribution of df 24 is 2,02 while the ES is good. This product also brings joyful teaching learning activity in the real classroom setting through matching game. Key words: teaching, vocabulary, sryphomat. Abstrak : Sryphomat adalah teknik untuk mengajar kosa kata, yaitu teknik kombinasi antara cerita, foto, dan permainan pencocokan. Tujuan dari teknik ini adalah untuk memperkaya kosakata siswa yaitu; kata benda, kata ganti dan kata sifat. Cerita digunakan untuk memperoleh kata, sementara foto-foto digunakan untuk memperoleh makna dari kata dalam cerita. Kemudian, permainan digunakan untuk memotivasi siswa agar lebih aktif dalam ruang kelas. ADDIE Prosedur digunakan untuk mengembangkan Sryphomat, proses dilakukan melalui analisis kebutuhan, desain, pengembangan, implementasi dan evaluasi. Dalam penelitian perkembangan ini, teknik telah diterapkan dikelas yang sebenarnya yang terdiri dari 24 siswa kelas enam SD Negeri 29 Kecamatan Pontianak Timur. Satu-Group Pretest Posttest dilakukan untuk mengetahui efektivitas Sryphomat terhadap peningkatan kosakata siswa. Hasilnya menunjukkan bahwa produk ini sangat efektif, t = 9,02 dan ES adalah 1,08. T-test lebih tinggi dari t- tabel distribusi df 24 pada 2,02 sedangkan ES baik. Produk ini juga membuat kegiatan belajar mengajar lebih menyenangkan melalui permainan menjodohkan. Kata kunci: pengajaran, kosa kata sryphomat